PERUBAHAN SIFAT KIMIA TANAH GAMBUT SETELAH PEMBERIAN LIMBAH PABRIK KELAPA SAWIT - Sulistiyanto Y.; Amelia V; Kamillah Kamillah; Rassyid M. A. (AgriPeat, 2015)
The purpose of this study was to assess changes of chemical properties of peat after being given a sewage of oil palm mill. The research was conducted from September to December 2014 at Analytical Laboratory University of Palangkaraya. This research is a quantitative way of measuring and comparing the chemical properties of peat were given sewage of oil palm mill, such as, boiler ash of palm oil mill (AB), wastewater of palm oil mill (LC), and oil palm empty fruit bunches (TK). AB dose used was 11.6 tonnes / ha, LC 1.800 L / 12 M2, and TK 20 tonnes / ha. Parameters measured were pH, available P, K-dd, Ca-dd, Mg-dd. Soil pH observations carried out at 0 weeks of incubation (0 MSI), 4 MSI, 8 MSI, 12 MSI, and 16 MSI. As for the P-Available, Ca-dd, Mg-dd, and K-dd performed at 0 MSI, 8 MSI, and 16 MSI. The results showed that treatment of AB on peat soil in 8 MSI showed the highest increase in available P and giving LC on peat soil in 8 MSI showed an increase in the value of the K-dd, Ca-dd, and Mg-dd